Clinical characteristics of patients with persistent postural-perceptual dizziness - Bittar,Roseli Saraiva Moreira (2015)
INTRODUCTION: Persistent postural-perceptual dizziness is the dizziness that lasts for over three months with no clinical explanation for its persistence. The patient's motor response pattern presents changes and most patients manifest significant anxiety. OBJECTIVE: To evaluate the clinical characteristics of patients with persistent postural and perceptual dizziness. METHODS: statistical analysis of clinical aspects of patients with persistent postural-perceptual dizziness. RESULTS: 81 patients, average age: 50.06 ± 12.16 years; female/male ratio: 5.7/1; main reasons for dizziness: visual stimuli (74%), body movements (52%), and sleep deprivation (38%). The most prevalent comorbidities were hypercholesterolemia (31%), migraine headaches (26%), carbohydrate metabolism disorders (22%) and cervical syndrome (21%). DHI, State-Trait Anxiety Inventory - Trait, Beck Depression Inventory, and Hospital Anxiety and Depression Scale questionnaires were statistically different (p < 0.05) when compared to controls. 68% demonstrated clinical improvement after treatment with serotonin reuptake inhibitors. CONCLUSION: Persistent postural-perceptual dizziness affects more women than men, with a high associated prevalence of metabolic disorders and migraine. Questionnaires help to identify the predisposition to persistent postural-perceptual dizziness. The prognosis is good with adequate treatment.